HUBUNGAN UMU DAN PENGETAHUAN DENGAN GAYA HIDUP SEHAT MAHASISWA AKPER YATNA YUANA LEBAK - sarma eko sinaga (MNJ (Mahakam Nursing Journal), 2018)
The purpose of this study was to see the relationship between age, knowledge and healthy lifestyle of AKPER Yatna Yuana Lebak students. The type of research is quantitative research with cross-sectional approach. The number of samples used is 147 respondents that are AKPER Yatna Yuana Lebak students that are still active and the type of sample used is simple random sampling. This research was conducted at AKPER Yatna Yuana Lebak, in December 2017. The independent variable in this research is age and knowledge while the dependent variable is a healthy lifestyle. The data collection technique was obtained by using a questionnaire. Data Analysis has been done using univariate analysis and bivariate analysis with Chi-Square statistics test. The age distribution of respondents was < 19 years old (76,7%), while the respondents were 19 years old (71,3%). While the distribution of knowledge of respondents that are not good is 63 (42,9%), while respondent’s knowledge of good respondents is 84 (57,1%). It results in statistic test for the variable obtained p-value=0,466, Hence there is no difference between proportion of occurrence of student having a healthy lifestyle between students < 19 years and ≥ 19 years old. And on the knowledge variable obtained p-value=0,190 it can be concluded there is no difference in the proportion of events between students that have a healthy lifestyle between students with good knowledge and students with less good knowledge. Keywords : Age, Healthy Lifestyle, Knowledge, Youth.